2022
DOI: 10.1177/2050313x211072967
|View full text |Cite
|
Sign up to set email alerts
|

Uterus didelphys with double vagina diagnosed during third cesarean section: A case report

Abstract: Uterus didelphys is a rare uterine anomaly. It is associated with fetal breech presentation, preterm delivery, and cesarean section. Longitudinal vaginal septum may be associated with uterus didelphys, which may cause dyspareunia and labor obstruction. We report a case of 28-year-old woman whose uterus didelphys and longitudinal vaginal septum were diagnosed during third cesarean section. This case report highlights the importance of routine examination of adnexal structures during cesarean section, so that an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The shorter vagina may be also involved in the closed vaginal phenotype. It is reported that a patient has the similar pathology of longitudinal vaginal septum, resulting in dyspareunia and obstruction [ 40 ]. Whether RA signaling is involved in the above process needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…The shorter vagina may be also involved in the closed vaginal phenotype. It is reported that a patient has the similar pathology of longitudinal vaginal septum, resulting in dyspareunia and obstruction [ 40 ]. Whether RA signaling is involved in the above process needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Mullerian defects are among a group of abnormalities that affect the genital and urinary system given the fact that they both share a common embryological origin (5,6). Uterine didelphys belongs to Mullerian duct anomaly class III as de ned by American society of reproductive medicine which includes adnexal adhesions and distal tubal occlusions among others (8).…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the least common Mullerian abnormalities (4). The mean incidence has been reported to be 8.4% globally (5). Following failed fusion of the paramesonephric ducts early in the pregnancy, there is formation of a longitudinal vaginal septum, two vagina, and two hemi-uteri each with its separate ovary and fallopian tube.…”
Section: Introductionmentioning
confidence: 99%
“…Preventive measures for uterus bicornis unicollis cases cannot correct the congenital abnormality but can optimize health quality of life through education, physical examinations, routine ANC, and regular monitoring to prevent early and advanced complications in both mother and baby [ 1 , 3 , 4 ]. A study found that uterine didelphys does not necessitate a cesarean section, instead fetal presentation does [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In uterine didelphys, management of childbirth can be done either by vaginally or through cesarean section [ 6 , 25 ]. However, this condition is associated with fetal breech presentation and is the most common indication for cesarean delivery in women with uterine didelphys [ 1 , 4 , 13 , 21 , 26 ] Furthermore, if no coexistent symptom present, additional treatment to uterine disorder is deemed unnecessary [ 6 ]. In this present case, the patient showed no particular symptom prior and was decided to be given an emergency cesarean section based on her history with two previous cesarean deliveries and the fetus’ breech presentation as seen in the ultrasonography examination imagery.…”
Section: Discussionmentioning
confidence: 99%